Simplified modelling of the performance of concrete tunnels during fire and post-fire damage classification - Ruben Van Coile; Balša Jovanović; Ranjit Kumar Chaudhary; Xavier Deckers; Andrea Lucherini (Acta Polytechnica CTU Proceedings, 2022)
The performance of concrete tunnel structures during and after fire is not well understood. This is an obstacle to the adoption of risk-based approaches for fire safety design of tunnel structures. Upon the request of the Belgian fire safety consultancy FESG, a simplified assessment of the collapse probability and post-fire damages for a reference tunnel structure has been made. The structural system is modelled through 2D beam finite elements, where spalling rates have been assumed based on available literature data. Structural stability is verified for both the heating and cooling phases of the fire. In those cases where the structure survives up to burnout, the residual deformations and thermal damage to the tunnel structure are assessed.